Nanometer-Ranged Interfacial Interactions of the VRFB-Cell Electrolyte Species: An Implication of Molecular Dynamics Simulation - Anant Babu Marahatta (International Journal of Electrochemistry)
In the large-scale energy storage technological sectors and many other state-of-the-art renewable energy subsidy policies, the vanadium redox flow battery (VRFB) stands as a low variable cost yet promising electrochemical assembly applicable to convert “all-vanadium” electrolyte stored chemical energy into electrical energy. Despite its ubiquitous attributes of grid-scale power storage and the remarkable charge–discharge cycles, there is still a dearth of MD simulation-based theoretical studies insighted into its Nafion-117 membrane-plunged electrolyte matrix comprising with the adjacent state polyvalent Vn+-hydrated complexes ([V (H2O)m]n+), monovalent HSO4− and H3O+ specimens, and the neutral H2O molecules. This specific simulation aiming at investigating very preliminary ideologies required for probing interfacial microstructures in the vicinity of SO3− conductive sites of the Nafion, most probable molecular/ionic obstructions or facilitations of their proton exchange rates, genius electrochemical impacts of the [V (H2O)m]n+ moieties in their mutual osmotic balance, disruption or maintenance of the hydrogen-bonded water channel across the electrolytic/polymeric matrices, etc., would be very crucial to the advancement of this battery technology. The RDF tools retrieved quantitative results presented herewith illuminate mainly the (a) predominant dynamics of the hydrated protons [H3O+] which when conducted H+ (proton) turn into Zundel [H5O2]+ and Eigen [H5O2+] states; (b) considerable water exchanging trends throughout the entire proton hopping occurring across the hydrogen-bonded water network; (c) outbound distributed water molecules and their reluctant propensities toward the central metal ion of the [V(H2O)m]n+; (d) absolute rejection of the predominant electrolyte ion HSO4− by all of those ionic specimens toward their chemical bonding affinities; (e) complete absence of the [V(H2O)m]n+ blockage in the proton exchange SO3− sites of the Nafion and the significant H2O/H3O+ number density retaining capacity of the latter into its hydrophilic tunnel. The author believes this article as a fundamental means of unveiling various interfacial complexities involved in driving the entire charge/mass transfer mechanisms of the VRFB cell.